STIFIn Method as Intelligence Machine in Enhancing Children's Intelligence Potential in Pesantren - Hasan Baharun; Syafiqiyah Adhimiy (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractThis article presents the role of STIFIn method as an intelligence machine for enhancing children's intelligence potential as learning innovation in pesantren. This method is a new learning innovation, developed by pesantren to find genetic potential or intelligence machine that exists in each santri through STIFIn test by scanning on the ten fingers. Strokes or fingerprint data are processed by a computer application to determine the hemisphere and dominant brain layer, and those are; Sensing, thinking, intuiting, feeling and instinct. By that, studies learning style can be found, so it is easy for enhancing children's intelligence in pesantren. This study adopts a qualitative research approach and uses a case study design with a multi-site approach. The study show that the strategiys carried out by educators at the three pesantren for enhancing santri intelligence potential through the STIFIn intelligence engine can be mapped as follows: my rival is my teacher, road to victory, the power of dream, a tribute to other, one step closer.AbstrakTulisan ini menyajikan tentang strategi metode STIFIn sebagai mesin kecerdasan dalam meningkatkan potensi kecerdasan anak sebagai bagian dari inovasi pendidikan di pondok pesantren. Metode ini merupakan inovasi baru dalam pembelajaran, yang dikembangkan oleh pesantren untuk mengenali potensi genetik atau mesin kecerdasan yang ada pada setiap individu santri melalui tes STIFIn, yaitu dengan melakukan scan pada sepuluh jari. Data guratan atau sidik jari diolah oleh aplikasi komputer untuk menentukan belahan dan lapisan otak dominan, yaitu; sensing, thingking, intuiting, feeling dan insting. Dengan begitu, akan ditemukan gaya dan tipe belajar siswa, sehingga mudah untuk ditingkatkan kecerdasannya. Penelitian ini menggunakan metode kualitatif jenis studi kasus dengan pendekatan multi situs. Hasil penelitian menunjukkan bahwa strategi yang dilakukan oleh guru dalam meningkatkan potensi kecerdasan anak melalui metode STIFIn pada tiga pondok pesantren adalah; my rival is my teacher, road to victory, the power of dream, a tribute to other, one step closer.How to Cite: Baharun, H., Adhimiy, S. (2019).   STIFIn Method as Intelligence Machine in Enhancing Children's Intelligence Potential in Pesantren. TARBIYA: Journal of Education in Muslim Society, 6(2), 233-250. doi:10.15408/tjems.v6i2.9247.